Modernidade e desamparo: reflexões a partir da teoria freudiana do social - Santos, Marcus Vinícius Oliveira (2013)
This work, as its title suggests, aims to discuss the relationship between modernity and helplessness, from the freudian theory of the social, that is, from the so-called sociological or anthropological texts that comprise the works of Freud. Initially, we will make a presentation about modernity, from different perspectives, and, moreover, we will formulate a brief description of what we understand as modern ideas, that is, the set of key assumptions that define modernity. After we discuss the relations between psychoanalysis, modernity and modernism, understood as a movement of criticism of modern assumptions. We will try, indeed, to question the argument for which there would be a shift in the freudian reading of modernity that produces a radical break with the modern ideas. As we want to demonstrate, perhaps it might be more appropriate to state the hybrid character of the freudian theory, according that it combine antagonistic tendencies, inextricably intertwined. Henceforth, we will investigate the statute of helplessness in freudian discourse. Our starting point is the discussion of helplessness in the biological registry from the Project of 1895. Moreover, we will consider the helplessness in the social registry, emphasizing how this condition would be consequent of the collapse of tradition and pre-modern conceptions, notably regarding the decline of a protective figure. In this conception, the helplessness would be structural and inherent to the inclusion of the subject in modernity. We will also explore the question of the destinies of helplessness. On the menu of the procedures to regulating the malaise indicated by Freud, the illusions appear as one of the possible alternatives, that is, as one of the ways to search for salvation. We will seek, finally, to show that the illusions comprise not only the framework of religious ideas, but also statements characteristics of other forms of worldview (Weltanschauung), highlighting some philosophical systems.